Quality of Instructional Media of Multilingual Thematic Digital Dictionary for Elementary School Students - Sang Ayu Made Diah Utami Putri; Ni Made Ratminingsih; I Gede Budasi (E-LINK JOURNAL, 2022)
This 21st century and globalization era bring changes in various aspects. The starting point of the implementation of technologies is affected due to human development focus. The starting point of technological developments in education can be seen from the media use in the teaching and learning process. Manifesting technology through the use of instructional media, such as PowerPoint, video, song or illustration is also important to help both teachers and students in the process of learning. Therefore, the development of a Multilingual thematic digital dictionary of PowerPoint-based that has been produced can be a good media in assisting students’ literacy skill since it develops based on the curriculum, is involved with technology, and provide vocabulary as the main content. In addition, this research aimed on finding the quality of a multilingual digital dictionary based on the evaluation form of quality and validity of the product by expert judgment. This research resulted in digital dictionary media product produced is considered very decent media of 0.91 point with excellent quality.Keywords: Instructional Media, Literacy, Digital Multilingual Thematic Dictionary, Quality